Pediatric cardiology symptoms, diagnosis, treatment - Haas, Nikolaus A.; Kleideiter, Ulrich (Thieme, 2015)
Enriched with the extensive experience of leading experts in this constantly evolving field, Pediatric Cardiology is a comprehensive reference that helps cardiologists stay up-to-date on important developments in the specialty. It includes basic principles, diagnostic strategies for specific diseases, and the newest interventional catheterization techniques, giving readers the tools to successfully manage all types of pediatric heart disease